2015
DOI: 10.1016/j.dib.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Data on electrical properties of nickel modified potassium polytitanates compacted powders

Abstract: Potassium polytitanates are new promising type of ferroelectric ceramic materials with high ionic conductivity, highly polarizable structure and extremely high permittivity. Its structure is formed by [TiO6] octahedral units to layers with mobile potassium and hydroxonium ions in-between. The treatment in solutions containing nickel ions allows forming heterostructured materials which consist of potassium polytitanate particles intercalated by Ni2+ ions and/or decorated by nickel oxides NiOx. This modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
4
4
0
Order By: Relevance
“…Figure shows the frequency dependence of the AC conductivity σ′ AC (ω) at different temperatures. As with other alkali titanates, ,,,, σ′ AC (ω) increases with ω and with T . For example, σ′ AC (ω) of K 0.8 Zn 0.4 Ti 1.6 O 4 spans from ∼8 × 10 –5 S/cm (25 °C) to ∼3 × 10 –3 S/cm (300 °C) at the highest ω. σ′ AC (ω) of Cs 0.7 Zn 0.35 Ti 1.65 O 4 is of similar magnitude.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Figure shows the frequency dependence of the AC conductivity σ′ AC (ω) at different temperatures. As with other alkali titanates, ,,,, σ′ AC (ω) increases with ω and with T . For example, σ′ AC (ω) of K 0.8 Zn 0.4 Ti 1.6 O 4 spans from ∼8 × 10 –5 S/cm (25 °C) to ∼3 × 10 –3 S/cm (300 °C) at the highest ω. σ′ AC (ω) of Cs 0.7 Zn 0.35 Ti 1.65 O 4 is of similar magnitude.…”
Section: Resultssupporting
confidence: 56%
“…Figure b,d,f shows that the reduced ε′( T ) at high f is accompanied by a gradual decrease in the loss tangent [tan δ­( T )] from the maximum value of 3 (10 2 Hz) to 0.5 (10 6 Hz). This magnitude of tan δ­( T ) is also common among several compositions of the alkali titanate. , …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…While these cases do not require high-temperature sintering, ,, the possibility of extensive structural transformation in protonic samples complicates the interpretation of the ionic conduction. Putting conductivity aside, because these ions also act as the charges/dipoles, their movement under alternating current in the form of interfacial polarization has contributed to a giant dielectric permittivity (up to 10 6 ). However, the link between conductivity and dielectric permittivity in structurally defined, but compositionally tuned, samples has remained scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, it was shown that potassium polytitanates (PPT), modified by d-metal (Me) containing salts and further calcined at high temperatures (700-950 C) allowed obtaining the ceramic composites characterized with high permittivity (up to 100) at high frequency (microwave) range, [13][14][15][16] which does not concede BaTiO 3 dielectric constant. It is important that, during the thermal treatment, the amorphous particles of modified potassium polytitanates have a tendency to form multiphase and heterostructured products characterized with increased polarizability and adhesion properties.…”
Section: Introductionmentioning
confidence: 99%